Extending in-competition Athletics injury and illness surveillance with pre-participation risk factor screening: A pilot study. Issue 2 (May 2015) - Edouard, Pascal; Jacobsson, Jenny; Timpka, Toomas; Alonso, Juan-Manuel; Kowalski, Jan; Nilsson, Sverker; Karlsson, David; Depiesse, Frédéric; Branco, Pedro
Abstract Objectives To explore the performance of retrospective health data collected from athletes before Athletics championships for the analysis of risk factors for in-competition injury and illness (I&I). Methods For the 2013 European Athletics Indoor Championships, a self-report questionnaire (PHQ) was developed to record the health status of 127 athletes during the 4 weeks prior to the championship. Physician-based surveillance of in-competition I&I among all 577 athletes registered to compete was pursued during the championships. Results 74 athletes (58.3%) from the sample submitted a complete PHQ. 21 (28%) of these athletes sustained at least one injury and/or illness during the championships. Training more than 12 h/week predisposed for sustaining an in-competition injury, and a recent health problem for in-competition illness. Among the 577 registered athletes, 60 injuries (104/1000 registered athletes) were reported. 31% of injuries were caused by the track, and 29% by overuse. 29 illnesses were reported (50/1000 registered athletes); upper respiratory tract infection and gastro-enteritis/diarrhoea were the most reported diagnoses. Conclusions Pre-participation screening using athletes' self-report PHQ showed promising results with regard to identification of individuals at risk. Indoor injury types could be attributed to extrinsic factors, such as small track size, track inclination, and race tactics.